ANALISIS EFISIENSI PEMASARAN BAWANG MERAH DI KECAMATAN DRINGU KABUPATEN PROBOLINGGO - Pratama, Triyan Bayu (Universitas Panca Marga, 2024)
Indonesia is one of the countries that has the potential to develop various products from horticultural crops. Of the various types of horticultural crops, there are several types of vegetables that are widely developed, one of which is shallots. The very long shallot marketing chain and the price difference at the level of marketing actors will have an impact on farmers' income. The purpose of writing this article is to determine the marketing efficiency of shallots in Dringu District, Probolinggo Regency. The marketing channel patterns discussed are marketing margins, market integration and price transmission elasticity. The results show that the marketing margin in the second channel (farmers to middlemen to out-of-town traders) is more efficient than the first marketing channel (farmers to retailers to final consumers). Onion marketing in Dringu Sub-district is included in the monopsony market, which is a form of market that has several sellers with only one buyer. From the results of the price transmission elasticity analysis, the elasticity value is 0.415, which is the value of the price transmission elasticity < 1 so it can be said that marketing is not efficient. Keywords: marketing efficiency, shallots, Dringu District, Probolinggo